The use of graphs in Malaysian companies’ corporate reports: A longitudinal study - Abdul Rahman, Azhar (Elsevier Ltd., 2014)
The purpose of this paper is to examine the nature and extent of voluntary disclosure of graphical information in the annual reports of 54 non-financial public listed companies in Malaysia using a longitudinal approach.The results show that the disclosure of graphical information in Malaysian companies’ annual reports has increased at an ‘average level’ over the thirty-year period. The majority of Malaysian companies prefer to use the bar graphs and the most frequently graphed variables are profit, turnover, earnings per share, and shareholders’ fund.The implications of this study are that: a) companies should be aware of the usefulness and advantages of providing graphical information for the benefit of various user groups; b) it may timely for the accounting regulatory bodies to propose a minimum/adequate level of graphical information using selected items of high importance to users of annual reports; and to formulate suitable guidelines in order to standardise the presentation of graphical information in annual reports of companies.